Chemical preparation and properties of calcium phosphate based materials for biomedical applications - Silva, Manuel António Martins da
Calcium phosphate-based materials, in particular hydroxyapatite-based ones,are among the most important materials for biomedical applications (bone graftsubstitutes, drug delivery systems, etc.). Owing to their compositional similaritywith respect to hard tissues, these materials show superior bioactive,osteoconductive, cell seeding and growth environment properties. Additionally,their capability to adsorb biological important substances like proteins, drugs,etc. makes them interesting materials to be used as drug delivery systems. Several studies on the effects of morphological aspects like particle size,shape, pore size and pore volume on the biological behaviour of calciumphosphate-based materials have shown that the properties of these materialscannot be considered merely on compositional aspects, but the role ofmorphological issues must also be taken into consideration. In the present work, calcium phosphate particles with a wide range of sizeswere produced by precipitation in calcium/citrate/phosphate solutions. It wasobserved that the manipulation of experimental conditions, namely the citrate-calcium ratio (Cit/Ca) and the pH of the solution, allowed to producehydroxyapatite particles either as nanosized particles, either as micrometricsized aggregates with particular shapes. The different sizes and shapes wereanalyzed in the framework of nucleation and growth phenomena and henceattributed to the development of different particle surface charge conditionsrelated to the adsorption of differently charged citrate species. The study of the preparation of calcium phosphate porous granules by spraydrying the suspensions of the various precipitated hydroxyapatite particles wasalso undertaken in the present work. The obtained results showed that thedifferent morphologies of the suspended hydroxyapatite particles havesignificant effects on the spray dried granules’ morphology and microstructure,thus accounting for different pore size and pore size distributions. Moreover,the study of the spray dried granules heat treatment demonstrated that not onlythe granules’porosity may be further modified but also its crystal phasecomposition. In view of the potential applications of the porous materialsprepared in this work such as drug, growth factors and stem cells carriers or aspromoter of cell adhesion, the present study points out to a wide range ofpossibilities for producing calcium phosphate porous granules with a differentschedule of morphological characteristics.